2015
DOI: 10.1111/epi.13116
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of epilepsy surgery between 1991 and 2011 in nine major epilepsy centers across the United States, Germany, and Australia

Abstract: Summary Objective Epilepsy surgery is the most effective treatment for select patients with drug-resistant epilepsy. In this article, we aim to provide an accurate understanding of the current epidemiologic characteristics of this intervention, as this knowledge is critical for guiding educational, academic, and resource priorities. Methods We profile the practice of epilepsy surgery between 1991 and 2011 in nine major epilepsy surgery centers in the United States, Germany, and Australia. Clinical, imaging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
112
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 31 publications
8
112
1
Order By: Relevance
“…We propose the following reasons for this trend:

An increasing proportion of difficult cases as the key reason for this phenomenon. Similar observations and suggestions have been provided by other publications7 9 10 33 and are substantiated in our own cohort: first, the proportion of patients with clear indications for surgical treatment decreased over time (figure 3: less patients with MTS, BT and temporal resections). Potential causes are a decreasing incidence of precipitating injuries leading to MTS6 (resulting in a decreasing prevalence after two decades of epilepsy surgery) and an increasing tendency to remove low-grade tumours without formal presurgical epilepsy diagnostics 34.

…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We propose the following reasons for this trend:

An increasing proportion of difficult cases as the key reason for this phenomenon. Similar observations and suggestions have been provided by other publications7 9 10 33 and are substantiated in our own cohort: first, the proportion of patients with clear indications for surgical treatment decreased over time (figure 3: less patients with MTS, BT and temporal resections). Potential causes are a decreasing incidence of precipitating injuries leading to MTS6 (resulting in a decreasing prevalence after two decades of epilepsy surgery) and an increasing tendency to remove low-grade tumours without formal presurgical epilepsy diagnostics 34.

…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with previous reports on increasing diagnostic facilities, increasing numbers of hospitalisations and video-EEG monitorings but stable surgical numbers 8 9 32. Another study even reported about a slight decrease in surgical numbers 33. This increasing gap was related to a declining proportion of patients proceeding to surgery in the smaller centres 8.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…If this is truly a localizing technique, it would be far more useful if it could identify a focus in patients with nonlesional/extratemporal epilepsy, where localization is much more difficult. Recent studies suggest that in the future, these patients will represent our surgical challenge, far more than TLE (8). One case study suggested that PK11195 (a less specific TPSO tracer) uptake was localizing in a patient with extratemporal epilepsy resulting from a cortical dysplasia (9).…”
mentioning
confidence: 99%